Lord Dunsany, H. P. Lovecraft, and Ray Bradbury : spectral journeys - Touponce, William F. (Studies in supernatural literature., 2013)
This is a comparative study of modernity in the works of Lord Dunsany, H.P. Lovecraft, and Ray Bradbury, noted writers of fantastic fiction. The books examines how these authors addressed modernity by creating short stories that were in some sense ""nostalgic"" for a lost time or imaginary culture that they called home.